Investigation of parameters of the working substance - low temperature plasma in the ionization resonator chamber of the RF reactive engine - Vdovin, V.S.; Zajtzev, B.V.; Kobetz, A.F.; Rudiak, B.I.; Bomko, V.A.; Lesnykh, M.S.; Zhuravlev, V.G.; Rashkovan, V.M.; Bazyma, L.A.; Basteev, V.A.; Belokon, V.I. (Вопросы атомной науки и техники, 2003)
This paper is the extension of investigations of the RF engine designed for orientation and stabilization of the spacecrafts orbit, and it is undertaken for measuring of plasma parameters of RF discharge in the ionization resonator chamber. The experiments were performed at the frequency of 80 MHz on the model engine, in which a length of coaxial line with shortening capacities at the ends was used as the ionization resonator chamber. As the result of the experiments, conditions of the RF discharge ignition in the resonator chamber are studied; dependencies of plasma density and temperature versus applied power and working body pressure are obtained for various gases. The measurements of the thrust were performed at the special-purpose test bench. The data obtained allow making a conclusion that further investigations in this direction hold much promise.